Model Penelitian Fiqih - Wardatul Usroh; Fikri Pratama; Maulidya Salsabila (Jurnal Multidisiplin Indonesia, 2023)
In terms of jurisprudence, fiqh is the science that explains sharia laws relating to the actions of the Mukalaf which are issued from detailed postulates. The Al-Quran is the kalamulah that was revealed to the Prophet Muhammad SAW and there are several sciences in the Al-Quran which needs to be studied and explained by the interpreter. The following are also various approaches to the study of Islamic law put forward by scholars, both in sharia and other sciences. Sharia law or Islamic law is one field of Islamic study that is widely known by the public. This study is considered important so that the existence of Islamic law or Islamic law remains known and plays a role in guiding and guiding Muslims on their journey. In the process of interpretation, experts propose characteristics and research models of Islamic law.